Η Παναγία Γαλακτοτροφούσα στην Ανθούσα Τρικάλων παρά τον Αχελώο Ποταμό - ΠΑΣΑΛΗ, Αφροδιτη (Byzantina Symmeikta, 2022)
The Virgin Galaktotrophousa (1799), the main church of an old monastery close to the village Anthousa near Trikala in the region of Aspropotamos, is a single-nave church with an abbreviated dome, lateral apses and a later narthex to the west. Above the narthex there was a chapel dedicated to the Beheading of Saint John the Forerunner. It is covered by a gabled roof from which the dome springs. The protrusion on the exterior of the tiled roof of the west part of the naos leads to the hypothesis that the narthex was vaulted, possibly with a shallow dome. The abbreviated form of the dome, the placement of a chapel above the narthex, and the latter’s shallow dome are common practices in the wider region of Aspropotamos